PEMANFAATAN GOOGLE SITES SEBAGAI MEDIA PEMBELAJARAN VIDEOGRAFI - Ariesta Kusuma, Ahmad Fauzi Anggi; Damay Nugroho, Gabriella Meisye; Aulana, Putry Earlyta (TRANSFORMASI, 2024)
The integration of technology in education, particularly within multimedia, has progressed substantially, with platforms like Google Sites playing a pivotal role. Google Sites provides user-friendly and adaptable tools for developing websites that function as educational resources. This platform enables educators to curate interactive and dynamic content, such as text, images, videos, and more, which students can conveniently access at any time and from any location. The aim of this study is to develop a videography-focused educational website to improve the skills of both academic and general users. By employing the ADDIE model, the usability evaluation yielded a score of 78% according to the conversion table, demonstrating its effectiveness as a supplementary learning tool.